Evaluation of the potential of doxorubicin loaded microbubbles as a theranostic modality using a murine tumor model. (June 2015) - Abdalkader, Rodi; Kawakami, Shigeru; Unga, Johan; Suzuki, Ryo; Maruyama, Kazuo; Yamashita, Fumiyoshi; Hashida, Mitsuru
Graphical abstract: Abstract: In this study, a novel phospholipid-based microbubble formulation containing doxorubicin and perfluoropropane gas (DLMB) was developed. The DLMBs were prepared by mechanical agitation of a phospholipid dispersion in the presence of perfluoropropane (PFP) gas. An anionic phospholipid, distearoyl phosphatidylglycerol (DSPG) was selected to load doxorubicin in the microbubbles by means of electrostatic interaction. The particle size, zeta potential, echogenicity and stability of the DLMBs were measured. Drug loading was ⩾92%. The potential of the DLMBs for use as a theranostic modality was evaluated in tumor bearing mice. Gas chromatography analysis of PFP showed significant enhancement of PFP retention when doxorubicin was used at concentrations of 10–82% equivalent to DSPG. The inhibitory effects on the proliferation of B16BL6 melanoma murine cells in vitro were enhanced using a combination of ultrasound (US) irradiation and DLMBs. Moreover, in vivo DLMBs in combination with (US) irradiation significantly inhibited the growth of B16BL6 melanoma tumor in mice. Additionally, US echo imaging showed high contrast enhancement of the DLMBs in the tumor vasculature. These results suggest that DLMBs could serve as US triggered carriers of doxorubicin as well as tumor imaging agents in cancer therapy.